Meningkatkan Hasil Belajar Matematika Melalui Pembelajaran Matematika Realistik Pada Siswa Kelas V SD Negeri 057761 Kwala Gebang - Rusli Rusli (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
One form of mathematics learning that is oriented towards mathematizing everyday experiences and applying mathematics in everyday life is Realistic Mathematics Learning. This research aims to find out that mathematics learning outcomes can be improved through a realistic mathematics approach for Class V students at SD Negeri 057761 Kwala Gebang. This type of research is classroom action research which is carried out in stages that include planning, action, observation and reflection. The data collected was analyzed using quantitative and qualitative analysis. The results of the research concluded that mathematics learning outcomes had increased through a realistic mathematics approach in class V students at SD Negeri 057761 Kwala Gebang, this can be seen from: (1) the increase in the average student mathematics learning outcomes, namely in cycle I, from 64.36 to 88 .2 in cycle II; (2) increasing the percentage of students who have completed their studies, namely in cycle I by 48% to 92% in cycle II; and (3) increasing student activity in the learning process in accordance with the observation sheet carried out during the research, namely student activity that is appropriate to learning has increased from cycle I by 51.77% to 72.88% in cycle II and decreasing student activity that is not appropriate with learning from cycle I of 20% to 9.33% in cycle II.